Teaching economics as a science: The 1930 Yale lectures of Ragnar Frisch - Olav Bjerkholt; Duo Qin (University of Oslo, Department of Economics, 2010)
This paper is prepared for the forthcoming publication of Frisch's 1930 Yale lecture notes, A Dynamic Approach to Economic Theory: The Yale Lectures of Ragnar Frisch (details at: http://www.routledgeeconomics.com/books/A-Dynamic-Approach-to-Economic-Theory-isbn9780415564090). As the lecture series was given just as the Econometric Society was founded in 1930. We provide as background, a blow-by-blow story of how the Econometric Society got founded with emphasis on Frisch's role. We then outline how the Yale lecture notes came into being, closely connected to Frisch's econometric work at the time. We comment upon the lectures, relating them to Frisch's later works and more important, to subsequent developments in economics and econometrics.
Keywords: B23; 330; History of econometrics; Ökonometrie; Wissenschaftliche Methode; Dogmengeschichte